Improving The Levels of Reading Skills Of Grade 1 Learners Through Story-telling Via Phone Calling - Abisado, Jimboy Abad (Future Science / FSH-PH Publications, 2024)
The study aimed to assess the effectiveness of storytelling via phone calling strategy to improve the levels of reading skills of Grade 1 pupils at San Miguel Elementary School, Schools Division of Zambales during the School Year 2022-2023. Further delimitation included the following: (1) levels of reading skills based on pre-test and post-test results of reading inventory; and (2) significant difference in the reading levels of the learners in pre-test and post-test result of reading inventory. This research undertaking used the One-Group Pre-Test and Post-Test Experimental Design where a single group was measured or observed before and after the intervention program. After careful evaluation of parental consent and the willingness of the students to undergo intervention program, the researcher purposively selected twenty-eight students under “frustration reading level”. The study used a two-tailed Wilcoxon Signed Ranks Test with an alpha level of 0.05. It means that there is a significant difference between learners’ reading levels in pre-reading and post-reading inventory indicating a positive effect of the intervention used to the learners in the “frustration reading level”. The marked increase of the performance of the Grade 1 pupils in the pre-test and post-test can be concluded that the intervention used came to play as factor. With that, storytelling via phone calling is effective and responsive as one of the strategies to use in reading. One of the recommendations is Storytelling via phone calling reading strategy could be used by other teachers also to improve the levels of reading skills of their learners as well, especially amidst pandemic where there is no face-to-face interaction between students and teachers.